Parallel and convergent dynamics in the evolution of primary breast and lung adenocarcinomas - Robert A. Gatenby; Jamie K. Teer; Kenneth Y. Tsai; Joel S. Brown (Communications Biology)
Abstract Cancer development requires an evolutionary transformation from mammalian cells fully regulated by and integrated into multicellular tissue to cancer cells  that, as single cell protists, are individually subject to Darwinian selection. Through genetic and epigenetic mechanisms of inheritance, the evolving cancer phenotype must acquire independence from host controls, downregulate differentiated functions that benefit the host but not individual cells, and generate phenotypic traits that increase fitness in the context of the selection forces within the local microenvironment. Here, we investigate this  evolutionary transition in breast (BRCA) and lung (LUAD, without EGFR, KRAS or BRAF driver mutations) adenocarcinomas using bulk mutation and expression data from the TCGA database. We define evolution selection for genes and molecular pathways based on 1) changes in gene expression compared to normal tissue, and 2) significantly larger or smaller observed mutation rates compared to those expected based on the gene size. We find BRCA and LUAD disable different genes and gene pathways associated with tissue-specific signaling and differentiated functions but promote common molecular pathways associated with cell cycle, cell-cell interactions, cytoskeleton, voltage gated ion channels, and microenvironmental niche construction. Thus, tissue-specific parallel evolution in early cancer development is followed by convergence to a common cancer phenotype.